Detection of sexually transmitted pathogens and co-infection with human papillomavirus in women residing in rural Eastern Cape, South Africa - Taku, Ongeziwe; Brink, Adrian; Meiring, Tracy L.; Phohlo, Keletso; Businge, Charles B.; Mbulawa, Zizipho Z.A.; Williamson, Anna-Lise (PeerJ, 2021)
South African women of reproductive age have a high burden of sexually transmitted infections (STIs), including human papillomavirus (HPV) infection. However, there is limited information on the prevalence of sexually transmitted pathogens in women from rural Eastern Cape Province, South Africa. The study aims at determining the prevalence of sexually transmitted pathogens and co-infection with high-risk (HR) HPV among women from rural Eastern Cape Province, South Africa. Methods. A total of 205 cervical specimens were collected from women aged 30 years from a rural community-based clinic. The samples were tested for a panel of pathogenic STIs [Chlamydia trachomatis (serovars A-K & L1-L3), Haemophilus ducreyi, Herpes Simplex Virus (Types 1 & 2), Neisseria gonorrhoeae, Treponema pallidum, Trichomonas vaginalis (TV), and pathobionts [Mycoplasma genitalium (MG), Mycoplasma hominis (MH) and Ureaplasma spp. (UP)] using a multiplex PCR STD direct flow chip assay through a manual Hybrispot platform (Master Diagnostica, Granada, Spain). HR-HPV detection was performed by Hybrid Capture-2 assay. Results. High-risk HPV prevalence was 32.2% (66/205) and HIV-1 prevalence was 38.5% (79/205). The overall prevalence of six pathogenic STIs was 22.9% (47/205), with TV having the highest prevalence (15.6%; 32/205). UP (70.2%, 144/205) and MH (36.6%, 75/205) were the most frequently detected pathobionts. Co-infection with 2 pathogens pathobionts was observed among 52.7% (108/205) participants. Of the six pathogenic STIs, three participants had more than one STI (1.46%) with the presence of MH and UP. HSV-2 (OR: 4.17, CI [1.184 14.690]) and HIV infection (OR: 2.11, CI [1.145 3.873]) were independent STIs associated with HR-HPV infection. Conclusions. The high prevalence of pathogenic STIs underscores the need to improve syndromic management policy by implementing effective strategies of prevention,
Keywords: HPV; Sexually transmitted pathogens; Treponema pallidum; Trichomonas Vaginalis; Mycoplasma genitalium; Mycoplasma hominis; Ureaplasma